In silico and in vitro anti-inflammatory evaluation of 2,6-bis-(3'-ethoxy, 4'-hydroxybenzylidene)-cyclohexanone, 2,6-bis-(3'-Bromo,4'-methoxybenzylidene)-cyclohexanone, and 2,6-bis- (3',4'-dimethoxybenzylidene)-cyclohexanone - Bambang Wijianto, Ritmaleni Ritmaleni, Hari Purnomo, Arief Nurrochmad (Journal of Applied Pharmaceutical Science, 2020)
The aim of this research is to design the new mono-carbonyl analogs of curcumin, synthesize the molecules, and determine its activity in cyclooxygenase inhibition in vitro and in silico. New design MACs were performed by the Quantitative Structure–Activity Relationship (QSAR) study using the BuildQSAR program. 2,6-bis-(3Ê¹-ethoxy, 4Ê¹-hydroxybenzylidene)-cyclohexanone, 2,6-bis-(3Ê¹-Bromo, 4Ê¹-methoxybenzylidene)-cyclohexanone, and 2,6-bis-(3Ê¹,4Ê¹ -dimethoxybenzylidene)-cyclohexanone had been synthesized using aldol condensation reaction. The anti-inflammatory assay was performed to measure the level of malondialdehyde. In silico studies were carried out to evaluate the activity of cyclooxygenase inhibition in cyclooxygenase-1 and cyclooxygenase-2 specific proteins. Molecular operating environment program was used for protocol docking. The results of the QSAR study reveal the good relationship of anti-inflammatory activities. The in vitro anti-inflammatory activities of 6-bis-(3Ê¹-ethoxy, 4Ê¹-hydroxybenzylidene)- cyclohexanone, 2,6-bis-(3Ê¹-Bromo, 4Ê¹-methoxybenzylidene)-cyclohexanone, and 2,6-bis-(3Ê¹,4Ê¹-dimethoxybenzylidene)- cyclohexanone indicate the promising potential to inhibit cyclooxygenase enzyme with IC50 13.53 μM, 11.56 μM, and 20.52 μM, respectively. The in silico evaluation showing that O atoms (47, from ketones) of 2,6-bis-(3Ê¹-Bromo, 4Ê¹-methoxybenzylidene)-cyclohexanone interact with ARG120 and TYR355 through H acceptor.
Keywords: In silico, in vitro, mono-carbonyl analogs of curcumin, anti-inflammatory, cyclooxygenase inhibition.